Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

L'économie sociale du point de vue des femmes - Corbeil, Christine; Descarries, Francine; Galerand, Elsa (LAREPPS, 2002)
Actes du colloque
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; discipline; division sexuelle du travail; périodes historiques; québec; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; économie; économie sociale

La résistance à la pénalité : un impératif féministe - Faith, Karlene (Criminologie, 2002)
À l’ère de la croissance galopante des prisons sous forme de complexe industriel en Amérique du Nord, les tensions idéologiques vacillent entre châtiment et mouvements en faveur d’une justice réparatrice ou transformatrice. Entre les désinstitutionnalistes, qui cherchent à réduire le nombre de personnes en prison, et les abolitionnistes pénaux, qui visent une transformation sociale, on retrouve nombre de féministes canadiennes. Les femmes au Canada sont désillusionnées suite à l’échec du gouvernement fédéral à mettre en pratique la vision de La création de choix, un rapport d’un groupe de travail sur l’emprisonnement des femmes, datant de 1990. Le gouvernement n’a pas non plus tenu compte des importantes recommandations de la juge Louise Arbour, dont l’enquête de 1996 sur les inconduites du personnel correctionnel met en lumière le non-respect des lois dans les prisons. En 2002, encore plus de femmes se retrouvent dans les prisons à sécurité moyenne ou maximale au Canada pour des crimes relativement mineurs. Les années 1990 nous ont fourni une bonne leçon sur la futilité de la réforme des prisons, tout spécialement au nom du féminisme. Dans l’avenir, les féministes devront impérativement contester les fondements de la pénalité imposée par l’État plutôt que de tenter de réformer une institution désuète.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; criminologie; discipline; femmes* en prison; histoire et politique; justice sociale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques

Unequal freedom: how race and gender shaped American citizenship and labor - Glenn, Evelyn Nakano (Harvard University Press, 2002)
The inequalities that persist in America have deep historical roots. Evelyn Nakano Glenn untangles this complex history in a unique comparative regional study from the end of Reconstruction to the eve of World War II. During this era the country experienced enormous social and economic changes with the abolition of slavery, rapid territorial expansion, and massive immigration, and struggled over the meaning of free labor and the essence of citizenship as people who previously had been excluded sought the promise of economic freedom and full political rights.After a lucid overview of the concepts of the free worker and the independent citizen at the national level, Glenn vividly details how race and gender issues framed the struggle over labor and citizenship rights at the local level between blacks and whites in the South, Mexicans and Anglos in the Southwest, and Asians and haoles (the white planter class) in Hawaii. She illuminates the complex interplay of local and national forces in American society and provides a dynamic view of how labor and citizenship were defined, enforced, and contested in a formative era for white-nonwhite relations in America.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; approches et analyses; cours; discipline; droits des femmes*; droits des personnes; histoire et politique; intersectionnalité; inégalités; pol4212; premier cycle; périodes historiques; racisme; racisme systémique; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis; études critiques de la race; études de genres

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Gender and the silences of social capital: Lessons from Latin America - Molyneux, Maxine (Development and Change, 2002)
Social capital has entered development policy thinking and practice in Latin America where it converges with the premises of a new development agenda that emerged in the 1990s. Women are often central to the forms of social capital that development agencies are keen to mobilize in poverty relief programmes, but the terms of women’s insertion into these programmes is rarely problematized. This article critically examines the gendered assumptions that govern efforts to build social capital, and explores some of the tensions that have arisen in post-transition Latin America between women’s rights and social capital agendas.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique latine; amériques; approches et analyses; discipline; droits des femmes*; inégalités; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Basics from Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis